The Influence of The Work Environment on Employee Performance - Alviara Citra Arbyan; Setyo Riyanto (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
The study aims to illustrate and analyze the impact of the work environment on employee performance. This research is the study of explanations. The data analysis used is a descriptive analysis and some linear regression analysis. Studies show that a descriptive analysis indicates that the respondents approved of the majority of physical and non-physical work environments that a company has improved employee performance. The results of a double regression analysis suggest that the physical environment of part-time labor has a significant impact on employee's performance and a non-physical work environment also has a significant impact on workers' performance. Test results show both the physical working environment simultaneously and the non-physical work environment has significant effects on employee performance.